PENGARUH MODEL CHILDREN LEARN IN SCIENCE (CLIS) DENGAN BANTUAN MEDIA WORDWALL TERHADAP KEMAMPUAN BERPIKIR KRITIS IPA TERHADAP SISWA KELAS V SEKOLAH DASAR - Virlee Isfa’lana Alfath; Fitri Nuraeni; Hisny Fajrussalam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Critical thinking is one of the essential 21st-century competencies that should be fostered from early education levels. In science learning, this skill enables students to analyze information, evaluate evidence, and solve problems logically. However, learning practices that are still teacher-centered and lack student engagement contribute to the low levels of critical thinking among elementary students. This study aims to examine the effect of the Children Learning in Science (CLIS) model assisted by Wordwall media on students’ critical thinking skills in science learning. The research employed a quasi-experimental method using a pretest-posttest control group design. The subjects were fifth-grade students from two classes, where the experimental class applied the CLIS model with Wordwall, while the control class used the Discovery Learning model. A critical thinking test was used as the research instrument, and the data were analyzed using N-Gain scores and an independent t-test. The results showed a significant improvement in the critical thinking skills of students in the experimental class compared to the control class. The CLIS stages encouraged deep thinking activities, while Wordwall enhanced interactivity and conceptual understanding. It can be concluded that the CLIS model supported by digital media is an effective strategy to improve critical thinking skills in elementary science learning.